Calliandra mayana (Leguminosae, Mimosoideae), a new narrowly endemic species from Campeche, Mexico - Hernández, Héctor M. M.; Gómez-Hinostrosa, Carlos (Phytotaxa, 2017)
A new species of Calliandra (Leguminosae, Mimosoideae, tribe Ingeae) from a restricted locality of Campeche, Mexico is herein described and illustrated. The species appears to be closely related to C. molinae, a species from Honduras, El Salvador and Nicaragua, from which it may be distinguished by being allopatric, and by a more limited development of suberose bark in stems and branches, comparatively smaller leaflets, consistently glabrous leaflets and corollas, and by the scarcely villous pods. Calliandra mayana appears to be restricted to an extremely small seasonally flooded savannah surrounded by tropical deciduous forest and, based on IUCN criteria, it is provisionally considered Critically endangered.